Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum